Effectiveness and safety of different types of ablation modalities in patients with atrial fibrillation: a bayesian network meta-analysis from randomized controlled trials - Fan Maitri Aldian; Visuddho Visuddho; Bendix Samarta Witarto; Andro Pramana Witarto; Jason Oktavian Hartanto; Yan Efrata Sembiring; Jeswant Dillon (Journal of Cardiothoracic Surgery)
Abstract Introduction Atrial fibrillation (AF) is the most common cardiac arrhythmia, which significantly contributes to morbidity, mortality, and a diminished quality of life. Despite advancements in pharmacological treatments, many AF patients do not achieve adequate symptom control with oral medications. This network meta-analysis seeks to provide comprehensive evidence to guide clinical decision-making and optimize ablation strategies for patients with atrial fibrillation. Methods This network meta-analysis (NMA) was conducted in accordance to PRISMA NMA Checklist of Items (PROSPERO No. CRD42024577782). A comprehensive search was performed across major literature databases (PubMed, Scopus, CENTRAL, ProQuest, and Web of Science) up to July 10, 2024. Data analyses were performed using Rstudio v.4.4.1 employing Bayesian NMA with random-effects models. Sensitivity, subgroup, and network meta-regression analyses were also conducted. SUCRA values were estimated to present the ranking of each treatment in the network. Meta-proportions with GLMM (Generalized Linear Mixed Model) also performed to analyze the safety outcomes. Results A total of 6332 AF patients from 46 randomized controlled trials (RCTs) were included. NMA demonstrate epicardial (surgical) approach, especially video-assisted thoracoscopic surgery (VATS) (OR 1.54; 95%CrI [1.03,2.38]; SUCRA 89.61) exhibited superiority to reduce the AF recurrence in AF patients. Hybrid epicardial-endocardial ablation (OR 1.51; 95% CrI [0.82,2.82]; SUCRA 85.7) had a similar freedom from AF rate to VATS. Subgroup and network meta-regression analysis revealed that AF type ((β -0.415; [-0.776;-0.042]) and AF duration (β 0.602; [0.066;1.079]) influence the freedom from AF rate. Meta-proportion indicated that surgical or hybrid ablation exhibited a higher risk of mortality (Prop = 5.07%), pericardial effusion (Prop = 4.35%), and phrenic nerve injury (Prop = 4.35%). Conclusion NMA demonstrated higher effectiveness of VATS and hybrid ablation in reducing the recurrence rate of AF. Despite complications associated with surgical and hybrid approaches have higher prevalence, type of complications encountered in this approaches are less diverse.